Implementation of the Waterfall Method for Designing Sisar (Archive Information System) at the National University: Implementation of the Waterfall Method for Designing Sisar (Archive Information System) at the National University - Fardila Inastiana; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
Often with the development of increasingly sophisticated times we are required to follow it. One of them is in making system that can be applied to the community in various ways to facilitate its use. In an organization/institution a system is needed to facilitate the regulation of incoming and outgoing data. Especially in the case of letter archiving. Because after conducting a case study at the National University Administration Bureau, it was found that managing the filing of letters was still done manually and was not well organized, therefore a neat and orderly information system was needed. In this archive system it is necessary to store, update incoming and outgoing letters and provide reports of incoming outgoing letters if needed. It is hoped that with the realization of this archive system, managing correspondence is more structured and helps in the complete information process.